Importance of controlling the degree of saturation in soil compaction - Tatsuoka, Fumio (2016)
n the typical conventional fill compaction, the dry density ρd and the water content w are controlled in relation to (ρd)max and wopt determined by laboratory compaction tests using a representative sample at a certain compaction energy level CEL. Although CEL and actual soil type affect significantly the values of (ρd)max and wopt, they change inevitably in a given earthwork project while CEL in the field may not match the value used in the laboratory compaction tests. Compaction control based on the stiffness of compacted soil in the field has such a drawback that the stiffness drops upon wetting more largely as the degree of saturation, Sr, of compacted soil becomes lower than the optimum degree of saturation (Sr)opt defined as Sr when (ρd)max is obtained for a given CEL. In comparison, the value of (Sr)opt and the ρd/(ρd)max vs. Sr - (Sr)opt relation of compacted soil are rather insensitive to variations in CEL and soil type, while the strength and stiffness of unsoaked and soaked compacted soil is controlled by ρd and “Sr at the end of compaction”. It is proposed to control not only w and ρd but also Sr so that Sr becomes (Sr)opt and ρd becomes large enough to ensue soil properties required in design.